Outbound as The Alternative Method to Have Fun Arabic Learning - Jauhar Ali (Arabic Education Program IAIN Pekalongan, 2018)
As muslims, we understand that Arabic language is very urgent for thedevelopment and improvement of our religious knowledge and practices. Manymuslim students have willingness to master the language to be able to communicateand understand religious texts, which are mostly written in Arabic. Most of them,however, are not interested in Arabic language class, due to the difficulties in terms ofpronunciation, reading, and writing. Understanding the expressions and grammaticalfeatures (al-Nahwu and Al-Sharf) are the other challenges that the students cannothandle in short time and the themes are boring. In brief, there is an assumption thatstudying Arabic is difficult.The questions, then, are how to change the assumption?, and what are the bestmethod and strategy for students in studying the language in an enjoyable, fun, andsupportive atmosphere? These questions show both reality and challenge, especiallyfor the Arabic language teachers and lecturers, that there is a need to change theconventional teaching of Arabic language and at the same time, to find a new methodand real actions to answer the above questions. This article offers a new method ofteaching which focuses not only on teaching of Arabic language but also enjoyable,fun, and full of spirit atmosphere. The method is called by â€œoutbound using fungamesâ€ or â€œoutbound fun gamesâ€.